2015
DOI: 10.1128/jb.00261-15
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Porphyromonas gingivalis W83 CRISPR-Cas Systems

Abstract: The CRISPR-Cas (clustered regularly interspaced short palindromic repeats/CRISPR-associated genes) system provides prokaryotic cells with an adaptive and heritable immune response to foreign genetic elements, such as viruses, plasmids, and transposons. It is present in the majority of Archaea and almost half of species of Bacteria. Porphyromonas gingivalis is an important human pathogen that has been proven to be an etiological agent of periodontitis and has been linked to systemic conditions, such as rheumato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 59 publications
1
22
0
2
Order By: Relevance
“…Furthermore, the CRISPR-Cas and associated CAS proteins system represents a unique system that provides prokaryotic cells, as P . gingivalis , adaption and protection from host defenses [54, 55]. Down-regulation of the genes PGN_1924-Cas2, PGN_1925-Cas1 may suggest a decrease in the defensive capability of P .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the CRISPR-Cas and associated CAS proteins system represents a unique system that provides prokaryotic cells, as P . gingivalis , adaption and protection from host defenses [54, 55]. Down-regulation of the genes PGN_1924-Cas2, PGN_1925-Cas1 may suggest a decrease in the defensive capability of P .…”
Section: Discussionmentioning
confidence: 99%
“…They provide adaptive immunity against foreign elements such as bacteriophages/viruses, plasmids and transposons. At least 95% of clinical strains from P. gingivalis harbours CRISPR arrays [41]. The presence of transposases and CRISPR-associated sequences in P. gingivalis [11] suggested that some parts of the P. gingivalis genome are mobile so that rearrangement or horizontal gene transfer from one strain to another can take place [20].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of transposases and CRISPR-associated sequences in P. gingivalis [11] suggested that some parts of the P. gingivalis genome are mobile so that rearrangement or horizontal gene transfer from one strain to another can take place [20]. In the P. gingivalis W83 genome, all four CRISPR regions were transcribed and one of them was active against dsDNA in vivo [41]. Probably the CRISPR-Cas system has developed as a protective system that verifies and selects DNA entering bacterial cells, helping them to regulate horizontal gene transfer [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustered regularly interspaced short palindromic repeats CRISPRs belong to a family of DNA sequences characterized by short direct repeats (DRs) that are separated by spacers [1]. Almost half (45%) of the species in Bacteria and the majority (80%) in Archaea contain CRISPR-Cas systems [2]. Through an adaptation process, the system is able to store memories of previous exposure to foreign DNA in the spacer sequences across generations of progenies [3][4][5].…”
mentioning
confidence: 99%